MALAY LANGUAGE IN STIE BINA KARYA - Haratikka, Haya (Linguistik, Terjemahan, Sastra (LINGTERSA), 2021)
Endangered language has a close meaning to language shift. The situation when the number of that language user is getting less. Endangered language is when the children of a family do not acquire their "mother tongue" any longer. Although, they live in the location where the language comes from. For example, the Malay tribe in Tebing Tinggi. Tebing Tinggi is inhabited by three significant tribes, Batak, Javanese, and Malay. Moreover, Tebing Tinggi was surrounded by the coastal area. Serdang Bedagai and Batu Bara were the Malay tribe that dominated this area. Sekolah Tinggi Ilmu Ekonomi Bina Karya (STIE) Bina Karya is an institute placed in Tebing Tinggi. Most of its students come from the local area, and those areas, Serdang Bedagai and Batu Bara area are Malay people. However, they were rarely found uttering the Malay language when talking at the campus. This qualitative research will see the language endangered in the Malay language in STIE Bina Karya students. This study took twenty-nine Malay students as the informants in STIE Bina Karya. By distributing the open-ended questionnaire, then analyzing it using the thematic analysis. After analyzing the data, the Malay language in STIE Bina Karya was invulnerable and severely endangered. The most factors come from 1) the small number of users, 2) bilingualism dominates the communication, 5) parents do not play an important role in teaching their generation the minority language(linguistic suicide).